Propagação de castanha-da-amazônia (Bertholletia excelsa Bonpl.) por mini e microestaquia, com auxílio de rizobacatérias (Bacillus spp.) - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
The Amazon is the planet’s largest area of tropical forest, presenting a rich biodiversity in its flora. In this context, we come across the interesting and important Bertholletia excelsa, whose wood and chestnut have great commercial value and are a source of income for forest people. The aim of this work is to evaluate the vegetative propagation of Bertholletia excelsa by the mini and micro-cutting technique, with the aid of Rhizobacteria (Bacillus spp). For this, seedlings of chestnut trees were decapitated and their sprouts were removed, excised and inoculated with the rhizobacteria mixes. The experiment was conducted in a completely randomized design, consisting of 6 treatments (5 treatments and controls) with 6 replications, with 1 mini-cutting for each replication. The analyzed variables were: survival, callus formation, mini-cutting root formation and length. According to statistical analisis, the survival of mini-cuttings treated with rhizobacteria x controls showed a significant difference (p-0,01), in the other variables there was no significant variation. The MAO5PB mix, consisting of MAOPB12A, 12K, 12L, 12J and 12C bacilli, through qualitative analysis, was selected as the most productive and the 5 bacteria that constitute it were molecularly identified: PB12A as Bacillus wiedmannii; 12K as B. paramycoides; 12L as Lysinibacillus fusiformis; 12J as B. paramycoides and 12C as Lysinibacillus fusiformis. With the results obtained in this research, it is possible to propagate B. Excelsa through mini-cutting technique with the aid of rhizobacteria and contribute to reducing the pressure on the forest, with the recovery of degraded areas, increase commercial production and favoring small producers in the wood production chain and B. Excelsa chestnut. In the second experiment, of micropropagation, the explants were nodal segments of shoots (200) of decapited plants, which were disinfested with a 1,5% solution (tested) of sodium hypochlorite, to establish the culture teh explants were inoculated in ½ Cytokinin-enriched MS tested with BAP dosages (1,5; 3,0; 4,5 and 6,0 mg. L -1) and failed to sprout at 6 months.
Keywords: Castanha-do-brasil - Amazônia; Castanha-do-brasil - Propagação; CIENCIAS AGRARIAS: RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL; Propagação; Isolamento; Mix